The Koori Growing Old Well Study: investigating aging and dementia in urban Aboriginal Australians. (June 2014) - Radford, Kylie; Mack, Holly A.; Robertson, Hamish; Draper, Brian; Chalkley, Simon; Daylight, Gail; Cumming, Robert; Bennett, Hayley; Jackson Pulver, Lisa; Broe, Gerald A.
ABSTRACT Background: Dementia is an emerging health priority in Australian Aboriginal communities, but substantial gaps remain in our understanding of this issue, particularly for the large urban section of the population. In remote Aboriginal communities, high prevalence rates of dementia at relatively young ages have been reported. The current study is investigating aging, cognitive decline, and dementia in older urban/regional Aboriginal Australians. Methods: We partnered with five Aboriginal communities across the eastern Australian state of New South Wales, to undertake a census of all Aboriginal men and women aged 60 years and over residing in these communities. This was followed by a survey of the health, well-being, and life history of all consenting participants. Participants were also screened using three cognitive instruments. Those scoring below designated cut-offs, and a 20% random sample of those scoring above (i.e. "normal" range), completed a contact person interview (with a nominated family member) and medical assessment (blind to initial screening results), which formed the basis of "gold standard" clinical consensus determinations of cognitive impairment and dementia. Conclusion: This paper details our protocol for a population-based study in collaboration with local Aboriginal community organizations. The study will provide the first available prevalence rates for dementia and cognitive impairment in a representative sample of urban Aboriginal people, across city and rural communities, where the majority of Aboriginal Australians live. It will also contribute to improved assessment of dementia and cognitive impairment and to the understanding of social determinants of successful aging, of international significance.